2017
DOI: 10.1016/j.bbamem.2017.02.008
|View full text |Cite
|
Sign up to set email alerts
|

Accumulation of phosphatidylcholine on gut mucosal surface is not dominated by electrostatic interactions

Abstract: The accumulation of phosphatidylcholine (PC) in the intestinal mucus layer is crucial for the protection of colon epithelia from the bacterial attack. It has been reported that the depletion of PC is a distinct feature of ulcerative colitis. Here we addressed the question how PC interacts with its binding proteins, the mucins, which may establish the hydrophobic barrier against colonic microbiota. In the first step, the interactions of dioleoylphosphatidylcholine (DOPC) with two mucin preparations from porcine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
22
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 24 publications
(23 citation statements)
references
References 28 publications
1
22
0
Order By: Relevance
“…PC appears to be the most abundant component of cellular membranes, comprising 40–50% of all cell phospholipids and found mainly in the outer leaflet of the plasma membrane [ 50 ]. Intestinal PC derives from the diet or from biosynthesis in the liver and enterocytes, followed by secretion into the intestinal lumen [ 50 , 102 ]. In mammals, the major means of PC biosynthesis are CDP-choline and the (phosphatidylethanolamine N-methyltransferase) PEMT pathways [ 50 , 103 ].…”
Section: Major Iecs’ Phospholipids Their Metabolism the Role In Ibd And Therapeutic Potentialmentioning
confidence: 99%
“…PC appears to be the most abundant component of cellular membranes, comprising 40–50% of all cell phospholipids and found mainly in the outer leaflet of the plasma membrane [ 50 ]. Intestinal PC derives from the diet or from biosynthesis in the liver and enterocytes, followed by secretion into the intestinal lumen [ 50 , 102 ]. In mammals, the major means of PC biosynthesis are CDP-choline and the (phosphatidylethanolamine N-methyltransferase) PEMT pathways [ 50 , 103 ].…”
Section: Major Iecs’ Phospholipids Their Metabolism the Role In Ibd And Therapeutic Potentialmentioning
confidence: 99%
“… 6 After translocation across the TJ complex, PC is first bound to membrane-associated mucin 3, from where it is handled to secretory mucin 2. 6 , 7 The PC–mucin 2 complex is capable of moving within the mucus distally along the colonic wall to the rectum. During this transport to the rectum, mucus PC can be broken down by ectophospholipases of the commensal bacterial flora similarly as was shown for Helicobacter pylori in the gastric mucosa.…”
Section: Introductionmentioning
confidence: 99%
“…It was shown that PC is translocated from systemic sources across tight junctions (TJ) to the luminal side of mucosal cells driven by a negative electrochemical gradient generated by the cystic fibrosis transmembrane conductance regulator (CFTR) [7]. After TJ translocation, PC is bound to membrane-associated mucin 3, from where it is handled to secretory mucin 2 [5,8]. The PC-mucin 2 complex moves within the upper mucus layer along the intestinal wall distally to the colon and rectum to provide sufficient hydrophobic protection against colonic microbiota.…”
Section: Introductionmentioning
confidence: 99%